Having It Both Ways? Sympathy and Self-Love in Thomas Jefferson’s Moral Philosophy - Vajda, Zoltán (FOCUS: Papers in English Literary and Cultural Studies, 2020)
A long-time concern in literary studies, the sentimental conception of sympathy as a subject of scholarly inquiry, has recently also become a subject of American cultural and intellectual history. Derived from eighteenth-century English empirical psychology, the theory of the senses and Scottish moral philosophy, sensibility and sentimentalism soon emerged giving priority to feeling and the senses over reason and rationality.